Copyright exhaustion : law and policy in the United States and the European Union / Péter Mezei, Szeged Law School, Hungary. - Mezei, Péter (Cambridge intellectual property and information law., 2022)
In the Second Edition of Copyright Exhaustion, copyright scholar Péter Mezei offers an expanded examination of copyright exhaustion, including its historical development, theoretical framework, practical applications, and policy considerations. He includes updated case law and statutory developments for the first-sale doctrine in the United States and in the European Union, covering both analogue and digital applications with an eye toward scrutinizing the common rejection of exhaustion in the resale of digital subject matter including computer programs, sound recordings, audiovisual works, and e-books. He advocates for a digital first-sale doctrine that would offer legal consistency to copyright law and a technologically feasible framework for content producers and consumers.